Investigating the factors that trigger airline industry purchase intention - Tarkang, MaryMagdaline EnowMbi; Alola, Uju Violet; Nange, Ruth Yunji; Ozturen, Ali (Springer, 2022)
As the main communication platforms for today's competitive air transportation market expands, airline websites need to be user friendly to trigger positive electronic word of mouth. Website quality constitutes an influencing factor in consumer behavior and decision-making. Therefore the purpose of this study is to test informarion-task-fit on etetronic word of month, purchase intention and website quality. The study tested the effect of information-task-fit on website quality, electronic word of mouth and purchase intention of users of Turkish Airlines. A total of 604 questionnaires was obtained online within six months, using a quantitative and cross-sectional approach. The proposed above relationships were evaluated via structural equation modeling. Results were as hypothesized, with the perception that the availability of information required by users on the website influence website quality, electronic word of mouth and purchase intention. The website quality also influenced users' intention to purchase and electronic word of mouth. These results offer insights into improving and maintaining website quality by making the website user friendly so as to attract greater audience. This study's comprehensive model is lacking in service airline literature, thus this is an added research on the influence of information-task-fit web information and design on supposed quality of service and intention to purchase. Managers should also maintain high standards by hiring professional website builders so as to increase their usage. This study provides implications for airline website quality. A conclusion and further studies are presented below.
Keywords: Information-task-fit; Website quality; Electronic word of mouth; Purchase intention